2012
DOI: 10.1021/jp212524f
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Dynamics of Organic Tethers Bound to MCM41-Type Surfaces from Solid State NMR Measurements

Abstract: The conformation and motions of organic chains bound to the surface of MCM41-type mesoporous silica materials are investigated in molecular detail. 2D heteronuclear correlation measurements in conjunction with relaxation measurements are used to infer both the orientation and the motions of the organic chains on the silica surface. In octyl-MCM41, proximity of octyl tether carbons to silanols is observed with the exception of the terminal carbons, pointing to slight chain bending which positions the center car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It is worthwhile to note the ammonium propylsilane present may also arise from protonation by the silanol groups and residual water on the silica surface . The pendent APS species have been previously shown to hydrogen bond with such silanol groups . Notably, the 15 N resonance at 44 ppm is not found in samples of APS-SBA15 synthesized by the more traditional route, via grafting 3-aminopropyl silane species, yet its chemical shift is consistent with an alkyl amine .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is worthwhile to note the ammonium propylsilane present may also arise from protonation by the silanol groups and residual water on the silica surface . The pendent APS species have been previously shown to hydrogen bond with such silanol groups . Notably, the 15 N resonance at 44 ppm is not found in samples of APS-SBA15 synthesized by the more traditional route, via grafting 3-aminopropyl silane species, yet its chemical shift is consistent with an alkyl amine .…”
Section: Resultsmentioning
confidence: 98%
“…The pendent APS species have been previously shown to hydrogen bond with such silanol groups. 31 Notably, the 15 N resonance at 44 ppm is not found in samples of APS-SBA15 synthesized by the more traditional route, via grafting 3aminopropyl silane species, 12 yet its chemical shift is consistent with an alkyl amine. 32 Postgrafting amination was conducted by grafting bromopropylsilanes onto the surface of SBA15 and reacting it with ammonia gas.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This review primarily focuses on studies published after the previously reported review articles on solid state NMR of biomineralization proteins [11–14], discussing other proteins which have now been well studied, describing new techniques which are being implemented, and providing a look to the future of both methodology and systems. Work investigating interactions of non-protein based molecules such as citrate [15], succinate [16], tethered chains [17], or liposomes [18] on or with inorganic materials provide interesting venues for comparison, have recently been reviewed [19], and are outside the scope of this review. Additionally, the inorganic mineral of the biominerals has been studied in some detail [16,20–25], but that will also not be covered here.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state NMR spectroscopy provided convincing spectroscopic evidence for the presence of the desired functional groups. [36][37][38] Fig. 5 shows the 29 Si solid-state NMR spectra of the samples; the three signals at À90, À100 ppm and À109 ppm were attributed to the Q 2 , Q 3 and Q 4 peaks.…”
Section: Resultsmentioning
confidence: 99%